Students' Perceptions on the Use of Vocabulary Memorization Quiz During English Learning Process at SMA Negeri 2 Painan - Putri, Rani Andika; Rani, Yati Aisya (Journal of English Language Teaching, 2024)
This study was conducted to find out students' perceptions of vocabulary memorization quiz as their warm-up activity. The researcher used a descriptive method with questionnaires to get answers about students' perceptions. The purpose of this study was to find out how students' perceptions are based on four aspects of perception when using a vocabulary memorization quiz as their warm-up activity before starting learning. The sample of this study was 30 students at SMAN 2 Painan. Students were asked to fill in 15 statements in the questionnaire by choosing answers between strongly agree, agree, disagree, and strongly disagree. The statements were related to attractiveness, effectiveness, relevance, and motivation. The results showed that most of the 30 students who became the research sample positively perceived the use of vocabulary memorization quiz. In particular, the attractiveness aspect with five statements obtained a total average score of 3.3, the effectiveness and relevance aspects with three statements each obtained a total average score of 3.2 and the motivation aspect with four statements obtained a total average score of 3.1. From the results of this study, students' perceptions of using vocabulary memorization quiz based on four aspects, namely attractiveness, effectiveness, relevance, and motivation, show a positive perception. Through this study, it can also be concluded that the vocabulary memorization quiz is effectively used as a warm-up activity in students' English learning because it increases enthusiasm and motivation and makes it easier for students to master English vocabulary.